2009
DOI: 10.1063/1.3266007
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal determination of thermal diffusivity and polymerization depth profiles of polymerized dental resins

Abstract: The degree and depth of curing due to photopolymerization in a commercial dental resin have been studied using photothermal radiometry. The sample consisted of a thick layer of resin on which a thin metallic gold layer was deposited, thus guaranteeing full opacity. Purely thermal-wave inverse problem techniques without the interference of optical profiles were used. Thermal depth profiles were obtained by heating the gold coating with a modulated laser beam and by performing a frequency scan. Prior to each fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Regarding independent validation of the depth profiles, although mechanical hardness measurements were not performed in the studies reported in this paper, the present thermal diffusivity depth profiles are similar in rate of increase and saturation depth to those obtained earlier on the same samples with a thin opaque coating on the surface and single-parameter reconstruction. 28 These facts point to the robustness of the inversion methodology. The simultaneously reconstructed optical absorption coefficient profiles show good anticorrelation with the thermal diffusivity profiles consisting of a steep decrease in the first 60 m followed by a slower decrease up to a final optical absorption value.…”
Section: -6mentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding independent validation of the depth profiles, although mechanical hardness measurements were not performed in the studies reported in this paper, the present thermal diffusivity depth profiles are similar in rate of increase and saturation depth to those obtained earlier on the same samples with a thin opaque coating on the surface and single-parameter reconstruction. 28 These facts point to the robustness of the inversion methodology. The simultaneously reconstructed optical absorption coefficient profiles show good anticorrelation with the thermal diffusivity profiles consisting of a steep decrease in the first 60 m followed by a slower decrease up to a final optical absorption value.…”
Section: -6mentioning
confidence: 98%
“…A similar trend was recently observed in the bulk thermal diffusivity value of the present resin, as measured with an opaque thin metallic coating on the surface leading to purely thermal diffusivity reconstruction without the ͑photothermally saturated͒ optical absorption coefficient. 28 Reasonably assuming that all changes in PTR signal after photopolymerization are due to inhomogeneities of the optical and thermal properties of the sample, arbitrary depth profiles for the optical absorption and thermal diffusivity can be reconstructed by numerically determining the optimal pair of ͑␤ f , g͒ and ͑␣ f , q͒ at each angular frequency, so that the assumed profile locally results in the experimentally observed PT wave signal amplitude and phase data.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various thermal‐wave imaging methods have been developed such as scanning photoacoustic microscopy 14, photothermal 15, 16 and thermoreflectance 17–19 microscopy as well as lock‐in thermography (LIT) 20–22. Thermal wave‐based measurement and imaging methods are used in a broad area of applications, ranging from non‐destructive evaluation (NDE) of materials 23, 24, biological and medical investigations 25, 26, testing of electronic devices 27, to materials research (see, e.g. , 28), with a resolution reaching down to the micro‐ and nanoscale 29–31.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal work by Mandelis and co-workers, 1 modulated PTR has also been used for thermal conductivity depth profile reconstruction of heterogeneous samples as case (surface) hardened steels, [2][3][4][5][6][7] functionally graded materials, 8 and partially cured dental resins. 9 In the last years, two works dealing with the application of modulated PTR to the simultaneous reconstruction of the in-depth varying absorption coefficient (a) and thermal diffusivity (D) of semitransparent heterogeneous samples have been published. 10,11 The aim of this work is to study the capability of modulated PTR to obtain simultaneously a and D in multilayered materials.…”
mentioning
confidence: 99%